PROSEDUR PENGUJIAN SUBSTANTIF AKUN HUTANG USAHA PT XYZ OLEH KANTOR AKUNTAN PUBLIK JEPTHA NASIB & JUNIHOL - Fikri Hidayat (2021)
Audit is an examination and evaluation activity carried out by an auditor on the financial statements of a company that has been made by the financial management section. The examination is carried out critically and systematically so that the fairness of the financial statements made can be assessed. In determining the fairness of the financial statements, it is determined based on generally accepted accounting principles. Substantive testing is one of the stages carried out by the auditor in the audit process, the purpose of doing substantive testing is to examine a detailed financial report on existing accounts and to gain confidence in the reliability of the accounting records in the financial statements. One of the substantive tests carried out is on the accounts payable account. The stages of substantive testing are asking for a detailed list of accounts payable, then entering it into a working paper, after that a sampling test is carried out which will be used for vouching and tracing will also be carried out. Substantive testing of accounts payable accounts is carried out so that there is no fraud committed by management on accounts payable in the financial statements. The fraud in question is that the amount of trade payables presented in the financial statements is lower than the amount of trade payables that should be. The conclusion from doing substantive testing of accounts payable to accounts payable at PT XYZ is unqualified.